Tafsir Tarbawi: Perspektif Pendidikan Islam dalam Memahami Ayat-Ayat Al Qur'an - Aulia, Muhammad Ghozil; Arif, Mahmud (QuranicEdu: Journal of Islamic Education, 2025)
This study aims to analyze the interpretation of tarbawi on the perspective of Islamic education. This researchers used a qualitative approach with a library study method. The data sources used include primary literature such as interpretation books and secondary literature in the form of books, journals, and relevant scientific articles. This study, using descriptive-analytical techniques, tries to understand and analyze the verses of the Qur'an that have educational aspects. Source triangulation is used in this study to validate the data collected to ensure the validity of the research findings. The study results indicate that the interpretation of tarbawi has important values ??that are currently relevant to be applied in modern education such as character formation, intellectual development and spiritual development. The interpretation of tarbawi can also provide holistic insight to build an education system based on Islamic values. This hope theoretically contributes to the development of interpretation studies, and applicatively strengthens the concept of education.